The effects of citrulline supplementation on athlete´s performance: systematic review - Silvia Burgos; Aysu Dursun; Valentin Emilio Fernández Elias (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: Citrulline is a non-essential amino acid that may enhance exercise performance and reduce soreness after exercise. This systematic review aims to determine the possible outcomes of L-citrulline of citrulline malate supplementation.